Atomic layer deposited HfZrO4-based memristive devices: annealing effect and multilevel storage capability - Ramesh, Rahul; Stathopoulos, Spyros; Kumar, Sanjay; Levene, Hannah; Yadav, Deepika; Tsiamis, Andreas; Prodromakis, Themis (Frontiers in Nanotechnology, 2026)
In this work, an atomic layer deposited (ALD) Hf1Zr1O4 (HZO)-based switching layer is investigated in the device structure of a TiN/HZO/TiN. The thickness of the switching layer is ∼10 nm, which was grown by the thermal ALD at 250 °C by a super-cycle approach. Both pristine and annealed (400 °C for 60 s in N2) devices exhibit stable bipolar resistive switching responses after an essential electroforming process. However, the annealed devices require a relatively higher forming voltage but significantly improved ON/OFF ratio than pristine devices, which can be due to a certain modification at the TiN/HZO interface. The significant improvement in the ON/OFF ratio is attributed to the formation of nano-crystallinity in the film and an increment in sub-oxide content. The X-ray photoelectron spectroscopy (XPS) analysis also reveals the formation of a significant amount of sub-oxide (HfO2-x and ZrO2-x) after the annealing process. Additionally, the pristine devices exhibit comparatively poor switching stability and show a systematic decrement in the hysteresis loop, i.e., 73% after 100 switching cycles, whereas only a ∼22% drop is observed with annealed samples that significantly enhance the device stability. Lastly, the annealed device exhibits high volatility towards multiple programmable states, which can be useful in the development of multilevel memory storage, in-memory computation, and neuromorphic computation.